Fichas técnicas para el uso eficiente del agua en arroz, para Perú - Dotto, Gilberto; Muñoz, Luis Armando; Graterol Matute, Eduardo Jose; Jiménez, Daniel; Bruzzone, Carlos (Bioversity International and the International Center for Tropical Agriculture, 2020)
These technical sheets describe six climate-smart management practices that lead to efficient use of water in rice cultivation in Peru. These practices were identified thanks to the use of data analysis and expert knowledge. The study to reach these practices was carried out in the Selva and Costa areas.